The beautiful Christmas tree - Zolotow, Charlotte, 1915-; Nascimbene, Yan (Boston [Mass.] : Houghton Mifflin, 1999)
Although his elegant neighbors do not appreciate his efforts, a kind old man transforms his rundown house and a small neglected pine tree into the best on the street.
New York Times.
School Library Journal.
Wilson's Children.
3.0.
3.0
K-3
Keywords: Christmas -- Fiction; City and town life -- Fiction; Trees -- Fiction; Christmas -- Fiction; City and town life -- Fiction; Trees -- Fiction